The dynamic relationship between multiple team membership and individual job performance in knowledge‐intensive work. (16th January 2018) - van de Brake, Hendrik J.; Walter, Frank; Rink, Floor A.; Essens, Peter J. M. D.; van der Vegt, Gerben S.
Summary: Many employees in modern, knowledge‐based organizations are concurrently involved in more than one team at the same time. This study investigated whether a within‐person change in such individual multiple team membership (MTM) may precede and may be predicted by changes in an employee's overall job performance. We examined this reciprocal relationship using longitudinal archival data from a large knowledge‐intensive organization, comprising 1, 875 employees and spanning 5 consecutive years. A latent change score model demonstrated that an increase in an employee's MTM was associated with a subsequent decrease in his or her overall job performance evaluations. By contrast, an increase in job performance was associated with a subsequent increase in an employee's MTM. Moreover, our results indicated that although an increase in an individual employee's MTM initially decreases his or her job performance, in the long run, this increase in MTM was associated with higher job performance. Together, these results suggest a dynamic association between an individual employee's MTM and his or her overall job performance, such that these variables are mutually connected in a highly complex manner over time.